A single dose of cocaine enhances prospective memory performance - Hutten, Nadia RPW (J Psychopharmacol, 2018)
BACKGROUND: Prospective memory is the ability to recall intended actions or events at the right time or in the right context. While cannabis is known to impair prospective memory, the acute effect of cocaine is unknown. In addition, it is not clear whether changes in prospective memory represent specific alterations in memory processing or result from more general effects on cognition that spread across multiple domains such as arousal and attention. AIMS: The main objective of the study was, therefore, to determine whether drug-induced changes in prospective memory are memory specific or associated with more general drug-induced changes in attention and arousal. METHODS: A placebo-controlled, three-way, cross-over study including 15 regular poly-drug users was set up to test the influence of oral cocaine (300 mg) and vaporised cannabis (300+150 ‘booster’ µg/kg bodyweight) on an event-based prospective memory task. Attentional performance was assessed using a divided attention task and subjective arousal was assessed with the Profile of Mood States questionnaire. RESULTS: Results showed that cocaine enhanced prospective memory, attention and arousal. Mean performance of prospective memory and attention, as well as levels of arousal were lowest during treatment with cannabis as compared with placebo and cocaine as evinced by a significantly increased trend across treatment conditions. Prospective memory performance was only weakly positively associated to measures of attention and arousal. CONCLUSION: Together, these results indicate that cocaine enhancement of prospective memory performance cannot be fully explained by parallel changes in arousal and attention levels, and is likely to represent a direct change in the neural network underlying prospective memory.